A versatile color and fluorescence pH sensor based on AIE and open-loop synergy effect: Crystal structure and its application in cell imaging. (June 2021) - Liu, Zengchen; Wang, Like; Zhu, Wenping; Ding, Yongjie; Liu, Shaohua; Wang, Quanzhong; Chen, Yahong
Abstract: In the paper, a novel aggregation-induced emission (AIE) target molecule derived from rhodamine 6G hydrazine and tetrastyrene carbaldehyde was synthesized and characterized. And the single crystal was obtained by high boiling solvent volatilization (DMF/H2 O) method, which is the first reported analogous compound single crystal. Inside the crystal structure, the limited benzene ring spinning was observed. By the change of pH, the special spiro structure opened, simultaneously, the fluorescence resonance energy transfer process (blue to orange yellow fluorescence, colorless to pink) between tetrastyrene and rhodamine 6G occurred. So the AIE target molecule can be used as an effective fluorescence and color probe for detecting H + (pH). Additionally, the cell fluorescence imaging experiment proved potentially that the AIE target molecule could detect the change of pH in organism. Moreover, the FRET sensing mechanism was concluded by fluorescence spectra and DFT calculation. Such studies provided important ideas for pH sensor based on AIE molecule. Highlights: A novel aggregation-induced emission (AIE) target molecule derived from rhodamine 6G group was synthesized. The AIE molecule exhibited color and fluorescence sensing property for H + . The fluorescence sensing mechanism was concluded by DFT calculation.